The Composite Materials for Localization of Volatile Radioactive Iodine Forms from Steam-Air Phase during Severe Accidents at NPPs - Kulyukhin, Sergey; Mizina, Lubov; Rumer, Igor; Mikheev, Nikolai (IntechOpen, 2011)
None